Phase diagram, crystal growth and superconductivity of CaLaBaCu3O7-y crystal - Chen, C; Wondre, F; Wanklyn, B; Hodby, J; Ryan, J (Chapman and Hall Ltd, 1999)
CaLaBaCu3O7-y (CLBCO) is a high T-c superconductor with unique tetragonal structure and cross-cationic substitution sites. In this paper, we present our study on the BaO-CuO-CLBCO phase diagram and its application to the crystal growth of CLBCO. The eutectic composition of BaO-CuO system is confirmed by the improved thermogravimetric analysis (ITGA) and is used for the crystal growth as a self-flux system. A pseudo-phase diagram of CLBCO-eutectic flux system is established by differential thermal analysis (DTA), which enables the selection of a suitable starting composition and temperature program for the crystal growth. We explore the relation between crystal growth, cell parameters and the main superconducting transition temperatures (T-c). The T-c of CLBCO crystals depends strongly on the Ca/La ratio in the starting materials. As for YBa2Cu3O7-y (YBCO), a small amount of BaF2 additive greatly increases the main transition temperature of CLBCO crystals. This can be understood by the cluster model we proposed previously for YBCO crystal growth. Based on the research on the phase diagram, crystal growth and the superconductivity, high T-c crystals of CLBCO with size up to 6.5 x 6.5 x 0.4 mm(3) have been grown from the eutectic self-flux system with BaF2 as additive. T-c was determined by an a.c. susceptibility measurement, which shows the main transition temperature up to 60 K for the as-grown crystals. After annealing in flowing oxygen at 600 to 400 degrees C for two days, T-c increased to 73 K.